Aggression Amongst Outpatients With Schizophrenia and Related Psychoses in a Tertiary Mental Health Institution - Jeyagurunathan, Anitha; Lau, Jue Hua; Abdin, Edimansyah; Shafie, Saleha; Chang, Sherilyn; Samari, Ellaisha; Cetty, Laxman; Wei, Ker-Chiah; Mok, Yee Ming; Tang, Charmaine; Verma, Swapna; Chong, Siow Ann; et al. (Frontiers in Psychiatry, 2022)
Abstract Aims: Aggression is defined as ‘any behavior intended to cause physical, emotional, or psychological harm to another’. The aims of the current study were to (i) examine underlying factor structure of the Buss-Perry Aggression Questionnaire (BPAQ)and (ii) explore socio-demographic and clinical correlates (symptom severity, substance use and alcohol use)among patients with schizophrenia and related psychoses in a multi-ethnic Asian population. Methods: Data collected from 397 participants who were seeking outpatient treatment for schizophrenia and related psychoses at a tertiary psychiatric hospital were included in the analyses. BPAQ a29-item, four-factor instrument that measures physical aggression, verbal aggression, anger and hostility was used to assess aggression. Data on socio-demographic variables, age of onset of illness, drug use, alcohol use and symptom severity were also collected. Confirmatory factor analysis (CFA) was performed to establish the underlying factor structure of the BPAQ. Multiple regression analyses were utilized to examine socio-demographic and clinical correlates of the BPAQ factors. Results: The mean age of the participants was 36.2 years (SD=10.9, range: 21 to 65). Factor structure obtained from the CFA indicated that the higher order four-factor solution had an acceptable fit to the observed data (WLSMV χ2 = 1025.35, df = 320, RMSEA=0.07, CFI=0.94, TLI=0.93, SRMR=0.05). Females had lower physical aggression and hostility scores as compared to males. Those with lower education had higher physical aggression scores compared to those with higher education. Participants who received a diagnosis after 30 years had higher physical aggression and anger scores compared to those who received a diagnosis at or before 20 years. Symptom severity was positively associated with higher BPAQ scores. Conclusion: The study findings demonstrated high internal consistency and applicable measurement factor structure of BPAQ in this study sample, making it an appropriate questionnaire for assessing aggressive behavior in this population. We also identified socio-demographic and clinical factors that were associated with aggression in patients with schizophrenia and related psychoses.